A novel hydrogenic spectroscopic technique for inferring the role of plasma–molecule interaction on power and particle balance during detached conditions. (14th January 2021) - Verhaegh, K; Lipschultz, B; Bowman, C; Duval, B P; Fantz, U; Fil, A; Harrison, J R; Moulton, D; Myatra, O; Wünderlich, D; Federici, F; Gahle, D S; et al.
Abstract: Detachment, an important mechanism for reducing target heat deposition, is achieved through reductions in power, particle and momentum; which are induced through plasma–atom and plasma–molecule interactions. Experimental research in how those reactions precisely contribute to detachment is limited. Both plasma–atom as well as plasma–molecule interactions can result in excited hydrogen atoms which emit atomic line emission. In this work, we investigate a new Balmer Spectroscopy technique for Plasma–Molecule Interaction—BaSPMI. This first disentangles the Balmer line emission from the various plasma–atom and plasma–molecule interactions and secondly quantifies their contributions to particle (ionisation and recombination) and power balance (radiative power losses). Its performance is verified using synthetic diagnostic techniques of both attached and detached TCV and MAST-U SOLPS-ITER simulations. We find that H 2 plasma chemistry involving H 2 + and/or H − can substantially elevate the Hα emission during detachment, which we show is an important precursor for Molecular Activated Recombination. An example illustration analysis of the full BaSPMI technique shows that the hydrogenic line series, even Lyα as well as the medium-n Balmer lines, can be significantly influenced by plasma–molecule interactions by tens ofpercent. That has important implications for using atomic hydrogen spectroscopy for diagnosing divertor plasmas.